2006
DOI: 10.1051/0004-6361:20053580
|View full text |Cite
|
Sign up to set email alerts
|

Neutral carbon and CO emission in the core and the halo of dark cloud Barnard 5

Abstract: Aims. The physical conditions and chemical structure in the dark cloud of Barnard 5 and its surrounding atomic halo is studied. The impact of the halo on the line emission emerging from the molecular cloud is investigated. Methods. We present observations of the [CI] 3 P 1 → 3 P 0 transition of neutral carbon and the low-J transitions of 12 CO and 13 CO. The CO maps extend from the core (A v > ∼ 7) to the northern cloud edge and into the halo (A v < ∼ 1). They are complemented by deeply integrated [CI] spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…PDRs exposed to weak FUV radiation fields have been studied in a few sources using [C i] emission (e.g. Maezawa et al 1999;Bensch 2006;Pineda & Bensch 2007) but never observed with velocity-resolved [C ii] before Herschel/HIFI. Cubick et al (2008) suggest that most of the [C ii] in our Galaxy originates in a clumpy medium exposed to an FUV field of χ 0 = 10 1.8 , which is larger than the upper limit determined for the majority of the observed components.…”
Section: Discussionmentioning
confidence: 99%
“…PDRs exposed to weak FUV radiation fields have been studied in a few sources using [C i] emission (e.g. Maezawa et al 1999;Bensch 2006;Pineda & Bensch 2007) but never observed with velocity-resolved [C ii] before Herschel/HIFI. Cubick et al (2008) suggest that most of the [C ii] in our Galaxy originates in a clumpy medium exposed to an FUV field of χ 0 = 10 1.8 , which is larger than the upper limit determined for the majority of the observed components.…”
Section: Discussionmentioning
confidence: 99%
“…1) The long equilibrium timescales under diffuse neutral conditions provide, in reverse, some resilience which might help pre-existing H 2 to weather the changes which occur. 2) Dark clouds have haloes (Wannier et al 1993;Bensch 2006) and it has been suggested that the molecules supposedly seen in diffuse clouds are actually located around and exchanging material with dark clouds (Federman & Allen 1991); this may be true in some cases, but complex trace molecules are also seen along sightlines which are quite well separated from the nearest dark material . 3) Perhaps most promisingly, turnover within diffuse neutral gas due to turbulence, rapidly cycling material through a very dense phase, may provide for much faster formation of H 2 and trace species (Glover & Mac Low 2005;Falgarone et al 2005), establishing high molecular fractions from scratch on short timescales.…”
Section: Lifetimes Of Diffuse Clouds and Their Hmentioning
confidence: 99%
“…For some cases, where geometry (Pound & Goodman 1997), selfabsorption (Li & Goldsmith 2003), or modeling of photodissociation regions ( Bensch 2006) allows, the atomic gas related to molecular clouds can be studied. Studying the hierarchical structure within molecular clouds requires a large spatial dynamic range which restricts useful observational data sets to galactic objects.…”
Section: Introductionmentioning
confidence: 99%